TLX3 regulates CGN progenitor proliferation during cerebellum development and its dysfunction can lead to autism - Surendran Parvathy; Budhaditya Basu; Suresh Surya; Rahul Jose; Vadakkath Meera; Paul Ann Riya; Nair Pradeep Jyothi; Rajendran Sanalkumar; Viviane Praz; Nicolò Riggi; Biju Surendran Nair; Kamalesh K. Gulia; et al. (iScience)
Summary: Tlx3, a master regulator of the fate specification of excitatory neurons, is primarily known to function in post-mitotic cells. Although we have previously identified TLX3 expression in the proliferating granule neuron progenitors (GNPs) of cerebellum, its primary role is unknown. Here, we demonstrate that the dysfunction of Tlx3 from the GNPs significantly reduced its proliferation through regulating anti-proliferative genes. Consequently, the altered generation of GNPs resulted in cerebellar hypoplasia, patterning defects, granule neuron-Purkinje ratio imbalance, and aberrant synaptic connections in the cerebellum. This altered cerebellar homeostasis manifested into a typical autism-like behavior in mice with motor, and social function disabilities. We also show the presence of TLX3 variants with uncharacterized mutations in human cases of autism spectrum disorder (ASD). Altogether, our study establishes Tlx3 as a critical gene involved in developing GNPs and that its deletion from the early developmental stage culminates in autism.